Modified Screen-Printed Microchip for Potentiometric Detection of Terbinafine Drugs - Menna El-Beshlawy; Hassan Arida (Journal of Chemistry)
The development of miniaturized microchips has widespread and growing interest in manufacturing potentiometric sensors with extremely valuable modifying response characteristics. In this context, here, we demonstrate microfabrication, electrochemical evaluation, and analytical applications of disposable thin-film potentiometric microsensors responsive to terbinafine antifungal medication. Miniaturized microchips have been realized by integration of the sensitive layer membrane modified by carbon nanotubes onto the surface of the plastic screen-printed microchip support using a new approach, which has been recently developed. The sensitive membrane comprises terbinafine HCl: ammonium heptamolybdate complex ion pair as ionophore, o-nitrophenyl octyl ether as a solvent mediator, potassium tetrakis (4-chlorophenyl) borate as an anion excluder, and polyvinyl chloride as support. The microsensor based on this plasticised sensitive membrane provides the Nernstian response and covers a wide concentration range of terbinafine of 10−8–10−2 mole·L−1. The merits offered by the elaborated terbinafine microchip over the bulk-based electrode include reasonable sensitivity (58.5 mV/concentration decade), fast response time (∼30 s.), long-term stability (4 months), integration, and automation feasibility. Furthermore, microfabricated terbinafine chips were successfully applied to the measurements of the investigated medication in some real samples with high accuracy (96.9%) and precision (<3%).